Language teachers’ identity development post COVID-19: a transformative learning perspective - Alosaimi, Muna (Frontiers in Education, 2023)
The COVID-19 pandemic has created enormous disruptions in the educational process. This led to radical shifts in teachers’ identities, roles, and practices. Despite the challenges and disruptions resulting from school closures, it could also be a great opportunity for teachers to learn and reshape their traditional roles and practices. Drawing on the poststructuralist view of teacher identity as multifaceted, continual, and socially situated, this study explores how COVID-19 reshaped and transformed seven EFL teachers’ professional identity post-school reopening at a Saudi university. To illustrate the trajectory of teachers’ identity development, Mezirow's Transformative Learning framework was employed, starting with COVID-19 as a disorienting dilemma that triggered critical reflection and transformations. Using a narrative inquiry approach, teachers reflected on their experiences via the Life Story Interview. Data were analyzed through reflexive thematic analysis, with a particular focus on professional agency as a conceptual lens to uncover how teachers maintain and develop their professional identity to meet the evolving demands of the post-pandemic teaching environment. The findings establish a nuanced conceptualization of identity transformation and development processes during times of change. These transformations manifested through three agentive dynamics in professional identity development: delegitimization, reconstruction, and empowerment. The insights gained from this research add to teacher education literature by outlining potential practicalities for promoting teacher identity development.